Diabetes self-care and its associated factors among elderly diabetes in the outpatient Department Hospital Universiti Sains Malaysia - Ishak, Nor Haslinda (2016)
Introduction: The world population is ageing and diabetes mellitus is one of the most prevalent diseases that afflict senior citizens. One of the reason of suboptimal glycemic control and diabetes complications is lack of self-care by those with diabetes. Objective: To describe diabetes self-care among elderly diabetic in the KRK, HUSM and to determine the associated factors. Material and method: A cross sectional study was conducted among elderly type 2 diabetes patients attending KRK, HUSM, Kelantan. Diabetes self-care was assessed using interview-based questionnaire the Malay Elderly Diabetes Self-Care Questionnaire (MEDSCaQ). Result: A total of 143 patients responded giving a response rate of 91.7%. The mean of total diabetes self-care score was 26.5 (SD 8.0), with minimum score of 1 and maximum score of 40. The factors with positive impact on diabetes self-care were being non-Malay (β=5.275, p=0.002), taken care by family during sick (β=8.995, p=0.004), higher family support (β=0.159, p=0.042), without neuropathy (β=3.261, p=0.016), acceptable knowledge in diabetes (β=4.375, p=0.001) and good knowledge in diabetes (β=5.893, p=0.004). However, having no CKD lowered diabetes self-care (β=-4.053, p=0.003). Conclusion: Race, care-taker during sick, family support, diabetes knowledge, neuropathy and CKD were significantly associated with diabetes self-care in elderly. These factors should be taken in account in planning future diabetes self-management programs among the elderly.